Efektivitas Penggunaan Kahoot sebagai Media Evaluasi Pembelajaran Mufradat bahasa Arab di LKP Kampung Arab Al-Azhar Pare - Ali Al Haddad; Munirul Abidin (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This research examines the effectiveness of using Kahoot as a learning evaluation medium for mufradat (vocabulary) in Arabic language at LKP Kampung Arab Al-Azhar Pare. The research background indicates that mastering mufradat is crucial in Arabic language learning, yet conventional teaching and evaluation methods are often monotonous and less motivating for students. The objective of this study is to test the effectiveness of Kahoot as an evaluation medium in Arabic language learning for students of Takallam 1 Program. The method used is a combination of qualitative and quantitative with a one-group pre-test-post-test experimental design on 24 students. Research findings show a significant increase in students' average scores from pre-test (35.6250) to post-test (83.5417) after using Kahoot , as well as positive responses from students stating that Kahoot is enjoyable, easy to use, and engaging. The implication of this research is that the use of Kahoot is effective in increasing motivation and learning outcomes of Arabic.